Abnormal ECG findings in athletes: Clinical evaluation and considerations - Abela, M.; Sharma, S. (Current Treatment Options in Cardiovascular Medicine, 2019)
Purpose of review: Pre-participation cardiovascular evaluation with electrocardiography is normal practice for most sporting bodies. Awareness about sudden cardiac death in athletes and recognizing how screening can help identify vulnerable athletes have empowered different sporting disciplines to invest in the wellbeing of their athletes. Recent findings: Discerning physiological electrical alterations due to athletic training from those representing cardiac pathology may be challenging. The mode of investigation of affected athletes is dependent on the electrical anomaly and the disease(s) in question. Summary: This review will highlight specific pathological ECG patterns that warrant assessment and surveillance, together with an in-depth review of the recommended algorithm for evaluation.